The limited (But relevant) role of the doctrine of the double effect in the just war theory - Rivera López, Eduardo Enrique (2017)
My focus in this paper is the use of the doctrine of double effect (DDE) in the context of Just War Theory. Different versions of DDE have different degrees of plausibility. Two distinctions are crucial. First, I distinguish between epistemically idealized and non-idealized scenarios. Second, I distinguish between versions of DDE that make a ceteris paribus comparison between intentional and non-intentional outcomes, from versions that either make a comparison that is not ceteris paribus or are non-comparative. After undertaking these classificatory tasks, I defend the following claims: First, in an idealized world, ceteris paribus versions of DDE are plausible. Second, we cannot transfer such plausibility to stronger (non-ceteris paribus) versions of DDE. Finally, in a non-idealized world, DDE is plausible. The argument for this last claim combines the reasons for defending ceteris paribus versions of DDE in idealized circumstances with an argument about how to proceed when we face hard choices under uncertainty.